A complicated relation. - Holmberg, Helena; Kulik, Zofia; Kwiek, Przemysław (Stockholm : Index - The Swedish Contemporary Art Foundation, 2012)
Kwiekulik ; Bratescu, Geta ; Grigorescu, Ion ; Hajas, Tibor ; Tamás, St.Auby ; Stilinovi, Mladen ; Todosević, Raša ; Trbuljak, Goran.
Index 7 September-23 October 2011, Kalmar konstmuseum 3 September-13 November 2011.
kunstcatalogus